2019
DOI: 10.26502/jsr.10020022
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Retirement Mentoring in Academic Surgery in the United States

Abstract: Background: Although successful retirement planning improves the well-being of retiring surgeons and facilitates effective succession strategies, the status of retirement mentoring in academic surgery remains unknown. The present study was designed to evaluate the presence of mentoring for retirement in the departments of surgery in the United States. Material and methods:A survey consisting of 5 questions (2 multiple choice; 3 yes/no) was sent to 170 chairs of departments of surgery in the United States in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…With accumulated life and professional experience, retired surgeons have developed a valuable perspective on the life and career of a surgeon. 1,2 This study evaluated retired surgeons' reflections on their lives and careers. Understanding what retired surgeons would have done differently in their past can Other self-reported regrets (179 [14.5%]) included more involvement in research, selecting better practice partners, being more adaptable to change, taking more risks, finding better mentors, spending more time with patients, saving earlier for retirement, having less 1-way institutional loyalty, asking more often for help, and paying more attention to institutional politics.…”
Section: Retired Surgeons' Reflections On Their Careersmentioning
confidence: 99%
See 2 more Smart Citations
“…With accumulated life and professional experience, retired surgeons have developed a valuable perspective on the life and career of a surgeon. 1,2 This study evaluated retired surgeons' reflections on their lives and careers. Understanding what retired surgeons would have done differently in their past can Other self-reported regrets (179 [14.5%]) included more involvement in research, selecting better practice partners, being more adaptable to change, taking more risks, finding better mentors, spending more time with patients, saving earlier for retirement, having less 1-way institutional loyalty, asking more often for help, and paying more attention to institutional politics.…”
Section: Retired Surgeons' Reflections On Their Careersmentioning
confidence: 99%
“…Indeed, multiple studies, including the rapid autopsy series referenced, implicate that local failure is associated with or directly contributes to death. [2][3][4] The high rate of local-only failure and associated poor survival necessitates therapies that improve local control. Postoperative chemoradiation may be one way to achieve this end, and results from the RTOG 9704 revealed that local recurrence occurred at a much lower rate (28%), supporting that postoperative chemoradiation reduces local failure.…”
Section: Comment and Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This information could be useful for mid-career surgeons looking for career guidance. One study of 53 surgery department chairs found that while nearly 80% considered retirement mentoring to be beneficial, only 3.8% of departments had a mentoring program for retired senior faculty, suggesting that this may be an area of growth for departmental support [1].…”
Section: Discussionmentioning
confidence: 99%